Output Ripple Difference and Following Lightweight Design of External Gear Pumps and Motors - Wang Hao; Song Anran; Li Yulong (Jixie chuandong)
In order to clarify the different output mechanism and following ripple difference between external gear pump and motor, based on the reverse design method from performance to gear parameter and special involute feature without undercut, from the contact ratio factor which can best reflect output ripple performance and trapped-oil performance, teeth number which can best reflect lightweight effect as constructed variables of involute profile, the function expressions of dimensionless normal length outside pitch circle and other involute profile parameters are derived, and then the ripple factor formulas of output flow for gear pump and output speed for gear motor are reconstructed. The minimum contact ratio factor and the minimum teeth number are determined by lightweight method under the allowable ripple factor. All results show that contact ratio factor is a key parameter that affects the output ripple, ripple factor of output speed is larger than that of output flow, the larger the contact ratio factor is, the smaller the ripple factor and the smaller the ripple difference is, but the larger the relief load of trapped-oil is; the contact ratio factor and teeth number are two key parameters affecting the lightweight effect, the greater the contact ratio factor or the fewer teeth, the better the lightweight effect; the minimum contact ratio factor is uniquely determined by the allowable ripple factor, and the minimum teeth number is determined by the minimum contact ratio factor, the limited addendum pressure angle and the limited addendum center angle, etc., thus, the existing conclusions on the ripple factor of gear pump/gear motor are improved.